Structural and functional analysis of Chitinase-IV of Brassica juncea: molecular modeling and dynamic simulation study. Issue 4 (4th March 2022) - Ayyamperumal, Selvaraj; Jade, Dhananjay; Tallapaneni, Vyshnavi; Mohan, Surender; Barge, Sagar; Moola Joghee, Nanjan; M. J. N., Chandrasekar
Abstract: Brassica juncea is an important oil seed crop. The productivity of this plant, however, is known to be low due to the attack of plant pathogens. The plant chitinase-IV is known to hydrolyse the chitin present in the cell walls of the plant pathogens and thus enhance the plant defense systems. In this connection, studies were carried out by us on the prediction and characterization of the 3D structure of chitinase-IV, the structural changes that take place when the protein is in complex with Allosamidin and the chitin fragments (Tri-oligosaccharide and N-acetyl glucosamine) that act as elicitors to induce plant innate immunity against the invading pathogens, and molecular dynamic simulation studies on the stability of these complexes. These studies are expected to give us an insight into the chitin-binding domain and information on the dynamics and energetics of the protein, which is not possible to obtain by experimental methods. The predicted 3D structure of the protein should give us a better understanding of the molecular function of the chitinase gene in Brassica juncea for devising better methods of biocontrol against fungal phytopathogens and harmful insects so as to increase the crop yield. Abstract : UF0001 Communicated by Ramaswamy H. Sarma